Social studies teachers' views of learner-centered instruction - YILMAZ, KAYA (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2008)
This study explored social studies teachers' views of learner-centered instruction and learning theories by employing the methods and procedures of the qualitative research tradition. In-depth, semi-structured interviews were conducted with the participants. The techniques and strategies of inductive qualitative data analysis were used to analyze the interview transcripts. The results showed that the participants had positive attitudes toward learner-centered instruction which they believed has the potential to make instruction engaging, enjoyable, involving, challenging, and relevant to students' learning. The teachers identified their teaching orientations more with the cognitive and constructivist approach than the behaviorist approach. The teachers' responses indicated the impact of the community on their views and practices.
Keywords: learner-centered; social studies; learning theories; constructivist; pedagogy; teacher knowledge; BELIEFS; EDUCATION